Australia and Canada in Afghanistan : perspectives on a mission - Maley, William, 1957-; Cunningham, Jack (Historian) (Toronto : Dundurn Press, 2015)
Afghanistan is a long way from both Canada and Australia, but from 2001, fate conspired to bring the three countries together. Following the attacks of September 11, 2001, Australia and Canada joined the U.S. and other Western allies in attacking al-Qaeda bases in Afghanistan. Operation Enduring Freedom began on October 4, 2001, but this was only the beginning of a much longer engagement in Afghanistan for both Canada and Australia, with a legacy much more ambiguous than the initial campaign had promised. Australia and Canada in Afghanistan: Perspectives on a Mission offers twelve essays from distinguished experts and decision-makers involved in the war. Wide-ranging in scope, their work offers fresh analyses of the Afghan War and on Australia's and Canada's contributions to it.
Afghanistan and its challenges / William Maley, Jack Cunningham -- Australian approaches to Afghanistan / William Maley -- Afghanistan, some lessons learned: a personal political perspective / Bill Graham -- Afghanistan, some lessons learned: a personal academic perspective / Adam Chapnick -- Afghanistan, post-2014: Pakistani perspectives / Samina Yasmeen -- The economic cost to Australia of the war in Afghanistan / Peter Hall -- The cost of the war in Afghanistan / J. Craig Stone -- Australian civil-military lessons from Afghanistan / Michael G. Smith -- Development: lessons learned from a decade in Afghanistan / Nipa Banerjee -- Shadows of the past: Commemorating the fallen in Australia and Canada / Kim Richard Nossal -- With the benefits of hindsight: chronicling Afghanistan errors / Ramesh Thakur -- The legacy of Canada's Afghanistan mission / Roland Paris.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Operation Enduring Freedom, 2001-2014.; Afghan War, 2001-2021 -- Participation, Australian; Afghan War, 2001-2021 -- Participation, Canadian; Afghan War, 2001-2021 -- Campaigns; Opération Liberté immuable, 2001-2014.; Guerre en Afghānistān, 2001-2021 -- Campagnes et batailles; Australia & New Zealand; HISTORY; Canada; Military; Military campaigns; Military participation -- Australian; Military participation -- Canadian; 2001